2015
DOI: 10.2147/vhrm.s92671
|View full text |Cite
|
Sign up to set email alerts
|

A comparative cohort study of totally laparoscopic and open aortobifemoral bypass for the treatment of advanced atherosclerosis

Abstract: BackgroundTotally laparoscopic aortobifemoral bypass (LABF) procedure has been shown to be feasible for the treatment of advanced aortoiliac occlusive disease (AIOD). This study compares the LABF with the open aortobifemoral bypass (OABF) operation.MethodsIn this prospective comparative cohort study, 50 consecutive patients with type D atherosclerotic lesions in the aortoiliac segment were treated with an LABF operation. The group was compared with 30 patients who were operated on with the OABF procedure for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…However, in patients with severe aortoiliac occlusive disease the changes in the hemodynamics have been shown to be less prominent probably due to a gradual development of collateral vessels secondary to AIOD [14]. Laparoscopic aortic surgery was introduced at Oslo University Hospital, Aker, in 2005 and after successfully conducting a prospective comparative cohort study during the earlier experience, a randomized multicentre trial, Norwegian Laparoscopic Aortic Surgery Trial (NLAST) is being performed [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with severe aortoiliac occlusive disease the changes in the hemodynamics have been shown to be less prominent probably due to a gradual development of collateral vessels secondary to AIOD [14]. Laparoscopic aortic surgery was introduced at Oslo University Hospital, Aker, in 2005 and after successfully conducting a prospective comparative cohort study during the earlier experience, a randomized multicentre trial, Norwegian Laparoscopic Aortic Surgery Trial (NLAST) is being performed [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with advanced atherosclerotic disease, it is sometimes necessary to perform additional procedures, for example, thromboendarterectomy of the groin arteries or even infrainguinal bypass, to ensure postoperative graft patency. We have previously, in a comparative cohort study design in the same patient population, found a significant relative reduction of the composite events (all-cause mortality, graft occlusion and systemic morbidity) in patients with LABFB as compared to open ABFB, during a median follow-up time period of 4.12 years 1. This may be due to the less-invasive nature of the LABFB procedure.…”
Section: Discussionmentioning
confidence: 77%
“…A median blood loss of 400 mL72 was reported as the lowest for the laparoscopic group, with a median of 725 mL5 being the most substantial amount of hemorrhage occurring. In the open group, the blood loss ranged from 9825 to 1010 mL 4.…”
Section: Resultsmentioning
confidence: 93%
“…One study did not report this outcome at all 70. Two studies found the difference between the two groups to be statistically significant,4,72 two did not report p -values,69,70 and in one paper, the difference did not reach statistical significance 5…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation